2010
DOI: 10.1063/1.3374031
|View full text |Cite|
|
Sign up to set email alerts
|

Direct determination of state-to-state rotational energy transfer rate constants via a Raman-Raman double resonance technique: ortho-acetylene in v2=1 at 155 K

Abstract: A new technique for the direct determination of state-to-state rotational energy transfer rate constants in the gas phase is presented. It is based on two sequential stimulated Raman processes: the first one prepares the sample in a single rotational state of an excited vibrational level, and the second one, using the high resolution quasi-continuous stimulated Raman-loss technique, monitors the transfer of population to other rotational states of the same vibrational level as a function of the delay between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The experimental setup used in this work is based on an apparatus originally used for high resolution Raman spectroscopy of vibrationally excited states, [13][14][15] that later evolved into a more elaborate setup for the determination of stateto-state rotational energy transfer rate coefficients. 16 For the observations described in this communication a simplified version of the latter setup has been used. The experiment follows a similar scheme to the ones used in the works of Orr (Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental setup used in this work is based on an apparatus originally used for high resolution Raman spectroscopy of vibrationally excited states, [13][14][15] that later evolved into a more elaborate setup for the determination of stateto-state rotational energy transfer rate coefficients. 16 For the observations described in this communication a simplified version of the latter setup has been used. The experiment follows a similar scheme to the ones used in the works of Orr (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…We will just provide a brief overview of the technique and refer the reader to Ref. 16 for a much more detailed description of the experimental apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three commonly used fitting laws have been examined. 6,11,35,55,56 The first of these, the exponential gap law (EGL), defines endothermic transfer events by the expression…”
Section: A Rotational Energy Transfermentioning
confidence: 99%
“…Laser induced fluorescence (LIF) from theà −X transition has been commonly used as the means to follow the populations in the vibrationally excited states. More recently, Doménech et al 6,7 have demonstrated the use of stimulated Raman scattering for this purpose.…”
Section: Introductionmentioning
confidence: 97%